ANALISIS DAN KELAYAKAN USAHATANI CABAI MERAH DI KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA - Siti Balkis dan Kosasih (Universitas 17 Agustus 1945 Samarinda, 2013)
The purpose of the research was to determine the red pepper farm income in Tenggarong Seberang Sub District, Kutai Kartanegara District. This research started on December 2011 until March 2012, with research location is in Tenggarong Seberang Sub District. The method that used is census method. The data needed by research are primary and secondary data. Primary data was derived from observation and interview with responder by using questionnaire which have been compiled in line wuth research. While secondary data was compiled from bibliography study and institution information which is related to research execution. The results of this research showed that: (1) Based on the survey result to 30 respondent obtained red pepper production to one season is 2.990,67 kg-1 mt-1 at the price of selling Rp 12.000 kg-1; (2) Total revenue farmers was Rp. 23.625.501,59 mt-1 ha-1 respondent-1 and total income from red pepper farming is Rp. 18.730.791,23 mt-1ha-1 respondent-1; and (3) Value of R/C ratio was 4,83 meaning that the cultivated red pepper farm is already profitable then planting a tomato can for resumes.